Contribution of surface and lateral forcing to the Arabian Gulf warming trend - Vasou, Panagiotis; Krokos, George; Langodan, Sabique; Sofianos, Sarantis; Hoteit, Ibrahim (Frontiers in Marine Science, 2024)
The contribution of surface and lateral forcing to the observed Arabian Gulf warming trend is studied based on the results of a high-resolution (1/100°, 60 vertical layers) MIT general circulation model (MITgcm) covering the period 1993–2021. The model validation against available observations reveals that the simulation satisfactorily reproduces the main features of the Arabian Gulf’s dynamics and their variability. We show that the heat content of the Arabian Gulf generally follows the reported variability of sea surface temperature, with significant increasing trends of 0.1 × 107 J m−3 and 0.2°C per decade. The interannual variability of the heat content is dominated by the surface heat fluxes, while the long-term warming of the basin is primarily driven by lateral fluxes. The analyses of the heat exchanges through the Strait of Hormuz indicate a pronounced upward trend in the transported heat toward the Arabian Gulf, which is associated with an increase in both the volume and temperature of the exchanged waters. Considering the inflow and outflow in the Strait separately, the temperature increase is more prominent in the inflowing waters; however, the dominant factor driving the rising trend in heat content exchanges is the increase in the volume of waters being exchanged. This implies that the observed warming of the Arabian Gulf during the investigated period is directly related to the acceleration of its overturning circulation.